The Clash of Values between April and Frank in their relationship in Richard Yates’ Revolutionary Road - Fenny Fenny; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This article tries to reveal the clash of value between April and Frank as the main characters in Richard Yates’ Revolutionary Road. Using the theories of gender role, power and motherhood, the analysis shows that April and Frank have different values even though they live in the same time, the1950s. The differences of values create a clash between them and it affects their relationship as husband and wife. April Wheeler as the strong character in this novel has modern values from her era while her husband expects her to follow the value of the1950s. These differences make them unable to fulfill their partner’s expectation. It can be concluded that because their values conflict each other, they have difficulties in their marriage life.